2011
DOI: 10.4081/cardiogenetics.2011.e3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for Hypertrophic Cardiomyopathy: Ongoing Voyage from Exploration to Clinical Exploitation

Abstract: More than two decades have elapsed since the discovery that sarcomere gene defects cause familial hypertrophic cardiomyopathy (HCM). Since then, genetic testing in HCM has developed and expanded, and is now widely available as a potential clinical service in the Western countries. In the meantime, however, the cross-talk between geneticists and clinicians has developed slowly, and still remains unstandardized, with modalities of interaction and degree of mutual comprehension that vary wildly in various setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…54 Thus, genetic test in the proband and cascade family screening is a valuable tool to exactly diagnose an inherited cardiomyopathy and to identify family members at disease-risk in preclinical stage. 55 Furthermore, bioinformatics approach and functional studies can help to predict the pathogenicity of new variants found during genetic screening. 56,57 In this regard, ESC and American Heart Association (AHA)/American College of Cardiology (ACC) guidelines [58][59][60][61] recommend molecular testing to improve the diagnosis and management of patients and at-risk family members.…”
Section: Genetic Basis Of Cardiac Diseases In Athletesmentioning
confidence: 99%
“…54 Thus, genetic test in the proband and cascade family screening is a valuable tool to exactly diagnose an inherited cardiomyopathy and to identify family members at disease-risk in preclinical stage. 55 Furthermore, bioinformatics approach and functional studies can help to predict the pathogenicity of new variants found during genetic screening. 56,57 In this regard, ESC and American Heart Association (AHA)/American College of Cardiology (ACC) guidelines [58][59][60][61] recommend molecular testing to improve the diagnosis and management of patients and at-risk family members.…”
Section: Genetic Basis Of Cardiac Diseases In Athletesmentioning
confidence: 99%
“…Similarly, in cases where new mutations are identified, targeted genetic tests can be designed, if needed, for screening family members at risk. Currently, different modes of cardiologist-geneticist interactions are being adopted in clinical settings around the world, a process that requires time, continuing education and to some extent, reorganization of health systems [64] . An example of such an evolving system of interdisciplinary interactions is that of the Egyptian National Genetic study of HCM ( Fig.…”
Section: Basic Principles In Molecular Geneticsmentioning
confidence: 99%